2021
DOI: 10.3389/fgene.2021.770742
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling of the Salt Stress Response in the Leaves and Roots of Halophytic Eutrema salsugineum

Abstract: Eutrema salsugineum can grow in natural harsh environments; however, the underlying mechanisms for salt tolerance of Eutrema need to be further understood. Herein, the transcriptome profiling of Eutrema leaves and roots exposed to 300 mM NaCl is investigated, and the result emphasized the role of genes involved in lignin biosynthesis, autophagy, peroxisome, and sugar metabolism upon salt stress. Furthermore, the expression of the lignin biosynthesis and autophagy-related genes, as well as 16 random selected ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 90 publications
1
18
0
Order By: Relevance
“…Interestingly, it seems that for some DHNs, there is preference for some architectures by stress. We investigated, for instance, the changes in expression under salt stress of different architectures in the leaves, shoots, and roots of three species ( Puccinellia tenuiflora Eutrema salsugenium, and Hordeum marinum ), according to the previously reported studies [ 50 , 51 , 52 ]. As shown in Figure 5 , YnSKn dehydrins are significantly more induced by salt stress than SKn in Puccinellia tenuiflora in leaves and roots with log2-fold changes reaching up to 5.63 and 3.44, respectively ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it seems that for some DHNs, there is preference for some architectures by stress. We investigated, for instance, the changes in expression under salt stress of different architectures in the leaves, shoots, and roots of three species ( Puccinellia tenuiflora Eutrema salsugenium, and Hordeum marinum ), according to the previously reported studies [ 50 , 51 , 52 ]. As shown in Figure 5 , YnSKn dehydrins are significantly more induced by salt stress than SKn in Puccinellia tenuiflora in leaves and roots with log2-fold changes reaching up to 5.63 and 3.44, respectively ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Expression data were collected from the previous reports [ 50 , 51 , 52 ]. Using gene IDs available in these studies, we have identified the protein sequences of dehydrins in the Phytozome v13 database and determined their architectures by using MEME.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the adjustment of metabolism and activation of the already existing enzymatic machinery could serve as a faster and more efficient strategy to cope with salt stress than the synthesis of new proteins (Pilarska et al, 2016 ; Figure 2 ). Furthermore, E. salsugineum exposed to 300 mM NaCl was used to investigate global transcriptional changes, and genes of several pathways mainly involved in lignin biosynthesis and accumulations of soluble sugars, as well as genes in autophagy and peroxisome pathways, were significantly enriched in the halophyte, suggesting these upregulated genes could contribute to salt tolerance of the halophytic Eutrema (Li et al, 2021 ).…”
Section: Gene Expression and Regulationmentioning
confidence: 99%
“…Furthermore, 64 E. salsugineum LEA proteins were identified to be classified into eight families, based on transcriptome sequencing, as well as the domain structures, numbers, and composition of conserved repeat motifs in LEAs. The remarkably induced expression of EsLEA1, EsLEA4, EsLEA6 , and EsDehydrin genes was revealed in leaves and/or roots, which implies that the expression of LEA proteins could be one of the important strategies for E. salsugineum to deal with salt stress (Li et al, 2021 ).…”
Section: Candidate Genes For Salt Tolerancementioning
confidence: 99%